A BRIEF OVERVIEW OF THE ISLAMIC WORLDVIEWAS THE MANIFESTATION OF AL-TAWḤĪD - Roslan Abd Jelani (DIRASAT: Jurnal Studi Islam dan Peradaban, 2019)
Islamic Worldview as an embodiment of ṭawḥīd is the main foundation of man in pursuing a goal that leads to perfect happiness (al-sa'ādah). It provides concepts that complement and prepare the way for this life and after. This research concerns the idea of worldview as a manifestation of ṭawḥīd. Using library research methods, it was found that: (1) Islamic Worldview provides an overview of two dimensions of life: the world and the hereafter; (2) Islamic Worldview emphasizes the importance of moral education which could produce in the human soul various emotions and sentiments that ensure the operation of the moral criteria by inspiration from the self.